Dyslipidemia varies among the metabolic phenotypes of polycystic ovary syndrome (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: The lipid profile among women with polycystic ovary syndrome (PCOS) is influenced by both insulin resistance and hyperandrogenism. The association of lipid profiles in metabolic phenotype-predominant women with PCOS was not adequately evaluated.Objective: To assess the association of lipid profiles among metabolic phenotypes [body mass index (BMI) and insulin resistance (IR)] between women with and without PCOS.Methods: This case-control study included 287 reproductive-aged females with PCOS and 190 age-matched controls conveniently sampled from the PCOS clinic, Department of Endocrinology of a University hospital, between September 2020 and August 2022. The fasting glucose, insulin, and lipid profiles were analyzed using glucose oxidase, chemiluminescence immunoassay, and glycerol phosphate dehydrogenase peroxidase methods. LDL cholesterol was calculated from Friedwald’s formula or measured directly. The National Cholesterol Education Program’s risk categories for different lipid fractions in Adult Treatment Panel III were used. Participants were divided into lean (